👤

1) 2√3*( √5-1)(√5+1)  + (2√3-5)² + ( 3√3 +2)²
2) [tex]( \frac{1}{ \sqrt{3} } + \frac{1}{3} ) ( \frac{ \sqrt{5} - \sqrt{3} }{ \sqrt{15} } + \frac{ \sqrt{4} - \sqrt{5} }{ \sqrt{20} } + \frac{ \sqrt{9}- \sqrt{4} }{ \sqrt{36} } ).[/tex]


Răspuns :

1). 2√3·(√5-1)(√5+1)+(2√3-5)²+(3√3+2)²=2√3(√5²-1²)+12-20√3+25+27+18√3+4=
=8√3+12-20√3+25+27+18√3+4=6√3+68
2). Pe prima o raționalizezi, la fel și pe celelalte cu radical, apoi aduci la același numitor și calculezi.
1). 2√3·(√5-1)(√5+1)+(2√3-5)²+(3√3+2)²=2√3(√5²-1²)+12-20√3+25+27+18√3+4=
=8√3+12-20√3+25+27+18√3+4=6√3+68